Child Care : Concerns and Conflicts ( A Reader) - Edited by Sonia Morgan and Peter Righton (London Hodder & Stoughton, 1989)
This collection of readings looking at policy issues, provision of services and practice in child care, is an integrated component of the Open University's multi-media course, Working With Children and Young People (K254). The course is non-racist and non-sexist, and challenges social class bias.
Include Index and Bibliography
Keywords: Child welfare -- Great Britain -- Child care